Meditations from Conversations with God an uncommon dialogue : Book 1 - Walsch, Neale Donald (Great Britain Hodder & Stoughton, 1991)
Offers selected passages for each day of the year from "Conversations with God," which argued that God is communicating with us all the time.
Keywords: Walsch, Neale Donald. God -- Miscellanea. Spiritual life -- Miscellanea. Imaginary conversations. God. Spiritual life